2002
DOI: 10.1016/s0020-7292(02)00184-4
|View full text |Cite
|
Sign up to set email alerts
|

Smoking as a risk factor for preinvasive and invasive cervical lesions in female sex workers in Venezuela

Abstract: The risk for FSWs to develop preinvasive or invasive cervical lesions increased with the number of cigarettes they smoked per day and their years of smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
1
0
3
Order By: Relevance
“…The impact of cigarette smoking on HPV prevalence has been assessed in both men and women [ 32 ]. However, in the current literature, little information is available regarding the difference in HPV infection between smoking and non-smoking FSWs, although it has been reported that the risk for FSWs to develop preinvasive or invasive cervical lesions increase with the number of cigarettes they smoked per day and their years of smoking [ 33 ]. In this study, the effect of smoking, either active or passive, on HPV infection was not demonstrated in FSWs in Shenyang and warrants further assessment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of cigarette smoking on HPV prevalence has been assessed in both men and women [ 32 ]. However, in the current literature, little information is available regarding the difference in HPV infection between smoking and non-smoking FSWs, although it has been reported that the risk for FSWs to develop preinvasive or invasive cervical lesions increase with the number of cigarettes they smoked per day and their years of smoking [ 33 ]. In this study, the effect of smoking, either active or passive, on HPV infection was not demonstrated in FSWs in Shenyang and warrants further assessment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Verificaram-se também uma dose de dependência com o número de cigarros e a diminuição da densidade das células de Langerhans (Barton et al, 1988). Resultados semelhantes foram observados por Nuñez et al (2002), em que as profissionais do sexo, fumantes há Acta Scientiarum. Health Sciences Maringá, v. 26, n. 2, p. 369-373, 2004 mais de 5 anos ou que fumam mais de 20 cigarros/dia, apresentaram um risco elevado de desenvolver neoplasia intraepitelial cervical (NIC) ou câncer invasor.…”
Section: Resultsunclassified
“…O tabagismo é um fator de risco associado tanto para a infecção genital de HPV como para o câncer de colo uterino (Nuñez et al, 2002;Winer et al, Acta Scientiarum. Health Sciences Maringá, v. 26, n. 2, p. 369-373, 2004 2003).…”
Section: Introductionunclassified
“…Sabe-se também que hábitos de vida saudáveis são essenciais para uma boa reposta imunológica do hospedeiro. O tabagismo é um fator de risco associado tanto para a infecção genital pelo HPV como para o desenvolvimento de câncer de colo uterino 17,18 . Muitos prontuários mostravam que a maioria das mulheres não fumava, e, em menor intensidade, também não ingeriam bebidas alcoó-licas.…”
Section: Revista Saúde E Pesquisaunclassified